Efek Berganda Demokrasi Pada Daya Saing Jawa Barat The Multiplier Effect of Democracy Effects on The West Java Competitiveness Index - Aurelia, Florence; R., Audra Tardas; Rif’at, M. Daffa; Maliki, M. Razaq (Blantika: Multidisciplinary Journal, 2025)
In the context of inter-regional competition, increasing regional competitiveness is a strategic issue in Indonesia. Although West Java Province recorded a high score in the Indonesian Democracy Index (IDI), its performance in the Regional Competitiveness Index (IDSD) still lagged, raising questions about the effectiveness of democracy in regional development. This study aims to analyze the relationship between the three dimensions of IDI freedom, equality, and capacity of democratic institutions and the twelve pillars of IDSD. The method used is a descriptive quantitative approach with bivariate correlation analysis using secondary data from BPS and BRIN in 2021–2023. The results show that the dimension of freedom is correlated with the pillars of infrastructure, financial system, market size, and innovation. The equity dimension is closely related to institutions, ICT, skills, and health. Meanwhile, the capacity of democratic institutions affects health institutions and services. These findings confirm that an inclusive and strong democracy has a significant contribution to encouraging regional competitiveness. This research is expected to be the basis for the formulation of sustainable democracy-based development policies at the provincial level.